PENDIDIKAN AQIDAH DALAM KULTUR MITOLOGIS - Ariwibowo, Gandung Agung; Tamyiz, Tamyiz; Arrohmatan , Arrohmatan (Jurnal Insan Cendekia, 2023)
Myth is a religious story that tells about the origin of gods, acts of nature, people or society and others. Sometimes the story is very important in the community who are not familiar with reading and writing as an oral tradition that is actualized in the form of ritual. The myths associated with a sacred story, namely primordial events that occurred in the beginning. Therefore the existence is mystery. Human cannot know their behavior if it is not manifest in humans. Myth is not the result of intellectual thought or logic. Taken into the nature of reality as event regularity, as part of reality as well as the reality of what happened. Reality is repeated that has meaning, while that cannot be repeated mean there is no meaning and is not called reality. This explanation is understood that the myth is interpreted as the accumulation of theology (Aqidah) education conceptions of imaginative musings about life, death, destiny, man, god, heaven, creation, etcetera are widely developed in Indonesian society, which was educated in religion by its parents, but cannot be separated from the mythological culture that has developed from generation to generation.